Impact of Canada - United States free trade on CARIBCAN countries - Higgings, John (Conference Board of Canada OttawaCA, 1988)
Examines the Free-Trade Agreement (FTA) in terms of its trade and investment diversion and its trade and investment creation effects. Concludes that trade under the CARIBCAN program will not be altered by the FTA and that trade creation effects may boost exports from the Caribbean region. Indicates that the FTA will spur investment in the region's manufacturing sector and investment diversion from the region will be marginal.